Biomaterial-assisted local and systemic delivery of bioactive agents for bone repair. (15th July 2019) - Zeng, Yuze; Hoque, Jiaul; Varghese, Shyni
Graphical abstract: Abstract: Although bone tissues possess an intrinsic capacity for repair, there are cases where bone healing is either impaired or insufficient, such as fracture non-union, osteoporosis, osteomyelitis, and cancers. In these cases, treatments like surgical interventions are used, either alone or in combination with bioactive agents, to promote tissue repair and manage associated clinical complications. Improving the efficacy of bioactive agents often requires carriers, with biomaterials being a pivotal player. In this review, we discuss the role of biomaterials in realizing the local and systemic delivery of biomolecules to the bone tissue. The versatility of biomaterials enables design of carriers with the desired loading efficiency, release profile, and on-demand delivery. Besides local administration, systemic administration of drugs is necessary to combat diseases like osteoporosis, warranting bone-targeting drug delivery systems. Thus, chemical moieties with the affinity towards bone extracellular matrix components like apatite minerals have been widely utilized to create bone-targeting carriers with better biodistribution, which cannot be achieved by the drugs alone. Bone-targeting carriers combined with the desired drugs or bioactive agents have been extensively investigated to enhance bone healing while minimizing off-target effects. Herein, these advancements in the field have been systematically reviewed. Statement of significance: Drug delivery is imperative when surgical interventions are not sufficient to address various bone diseases/defects. Biomaterial-assisted delivery systems have been designed to provide drugs with the desired loading efficiency, sustained release, and on-demand delivery to enhance bone healing. By surveying recent advances in the field, this review outlines the design of biomaterials as carriers for the local and systemic delivery of bioactive agents to the bone tissue. Particularly, biomaterials that bear chemical moieties with affinity to bone are attractive, as they can present the desired bioactive agents to the bone tissue efficiently and thus enhance the drug efficacy for bone repair.